β-Elemene promotes ferroptosis and reverses radioresistance in gastric cancer by inhibiting the OTUB1-GPX4 interaction - He, Jiancheng; Li, Ming; Bao, Jiapeng; Peng, Yifeng; Xue, Wanjiang; Chen, Junjie; Zhao, Jun (Frontiers in Pharmacology, 2024)
β-Elemene, extracted from Curcuma zedoaria (Wenyujin), has been used clinically to treat various cancers due to its ability to induce apoptosis, inhibit cell cycle progression, and reverse chemotherapy resistance. However, its effects on radioresistance in gastric cancer (GC) remain unclear. In this study, radioresistant GC cell lines MKN45/IR and AGS/IR were established through multiple low-dose radiations. Radiosensitivity was assessed via CCK-8 and clonogenic assays following treatment with β-elemene and specific inhibitors. Ferroptosis markers such as ROS, MDA, and Fe2+ levels were measured, and the impact of β-elemene on GPX4 and its interaction with OTUB1 was analyzed using qRT-PCR, Western blot, immunofluorescence, co-immunoprecipitation, and in vivo studies. Our results demonstrate that β-elemene reverses radioresistance in GC cells and, when combined with radiotherapy, significantly inhibits cell growth. β-Elemene treatment increases ROS, MDA, and Fe2+ levels, indicating enhanced ferroptosis, and inhibition studies with Ferrostatin-1 and Deferoxamine confirm the involvement of the ferroptosis pathway. Mechanistic investigations reveal that β-elemene disrupts the OTUB1-GPX4 interaction, leading to increased ubiquitination and degradation of GPX4, thereby promoting ferroptosis. In vivo studies further show that β-elemene combined with radiotherapy significantly suppresses tumor growth compared to radiotherapy alone. These findings suggest that β-elemene is a potent modulator of radioresistance in GC, primarily through its effects on the GPX4 pathway and induction of ferroptosis, highlighting its potential as a therapeutic adjunct in radiotherapy for resistant GC cases.